A Case Report on Management of Amavata w.s.r Rheumatoid Arthritis (International Journal of Ayurveda and Pharma Research, 2024)
Amavata is a term from Ayurveda, an ancient system of medicine from India. It describes a condition that resembles rheumatoid arthritis, where a person experiences joint pain, swelling and stiffness. The word Amavata comes from two words: “Ama” which means toxins and “Vata’’ which refers to one of the body’s fundamental energies, often associated with movements and wind. Early diagnosis and management of the disease is the only way to reduce the chances of deformities and morbidity caused by the disease. In Ayurveda a number of treatment modalities have been mentioned to treat Amavata. Panchkarma is very important and one of the eminent treatments explained in classical text. Current case study was done on female patient of 45 year with complaints of pain and inflammation in multiple joints (bilateral ankle joints, wrist joints). She was diagnosed with rheumatoid arthritis 6 year ago. In this case study patient was given Shodhana therapy with Erandmooladi Niruha Basti and Prasarini Taila Anuvasana Basti along with Shamana Chikitsa (Bhasma Vati). The patient got marked relief from this treatment.